2023
DOI: 10.1177/25168657231184665
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Covid-19 Infection During Pregnancy and Differential DNA Methylation in Human Cord Blood Cells From Term Neonates

Abstract: Background: The global pandemic of coronavirus disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). About 18.4% of total Covid-19 cases were reported in children. Even though vertical transmission from mother to infant is likely to occur at a low rate, exposure to COVID-19 during fetal life may alter DNA methylation patterns with potential long-term effects. Objective: To determine if COVID-19 infection during pregnancy alters the DNA methylation patterns in umbili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
0
0
Order By: Relevance
“…Because its level creases sharply in the plasma of COVID-19 patients, it was proposed as a potential me olomic biomarker [85,86]. XYLB was also identified among the top hypermethylated ge [87]. XYLB (xylulokinase) catalyzes the ATP-dependent phosphorylation of D-xylulose to produce xylulose 5-phosphate (Xu5P), which is a key regulator of glucose metabolism and lipogenesis [83].…”
Section: Genes/proteins Identified By 1-l Transcription Of C-(aa)n-n ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Because its level creases sharply in the plasma of COVID-19 patients, it was proposed as a potential me olomic biomarker [85,86]. XYLB was also identified among the top hypermethylated ge [87]. XYLB (xylulokinase) catalyzes the ATP-dependent phosphorylation of D-xylulose to produce xylulose 5-phosphate (Xu5P), which is a key regulator of glucose metabolism and lipogenesis [83].…”
Section: Genes/proteins Identified By 1-l Transcription Of C-(aa)n-n ...mentioning
confidence: 99%
“…Because its level decreases sharply in the plasma of COVID-19 patients, it was proposed as a potential metabolomic biomarker [85,86]. XYLB was also identified among the top hypermethylated genes [87].…”
Section: Genes/proteins Identified By 1-l Transcription Of C-(aa)n-n ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Increased morbidity and mortality in pregnant women and newborns is recognized for many years with viral infections during pregnancy, therefore, even at the beginning of the pandemic both pregnant women and newborns were considered at high risk for SARS-CoV-2 infection and its complications. Soon after pandemic onset, reports coming first from China and thereafter from all over the world described adverse outcomes of COVID-19 during pregnancy: increased rates of prematurity, stillbirth, fetal death, intrauterine growth restriction (IUGR), fetal distress, maternal respiratory failure (with increased need for oxygen, respiratory support, and intensive care unit admission), preeclampsia, C-section delivery, and maternal and neonatal death as compared to non-exposed pregnancies [16][17][18][19][20][21][22][23][24]. Studies also reported an even more complicated course of COVID-19 in pregnancies complicated with lung, cardiovascular, renal, and liver conditions, high blood pressure, diabetes, obesity, anti-phospholipidic syndrome, and thrombophilia [9,25].…”
Section: Introductionmentioning
confidence: 99%